2019
DOI: 10.1177/1352458519891984
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive processing speed in pediatric-onset multiple sclerosis: Baseline characteristics of impairment and prediction of decline

Abstract: Background: Cognitive impairment occurs in approximately one-third of pediatric-onset multiple sclerosis (POMS) patients. The Symbol Digit Modalities Test (SDMT), a widely used cognitive screen in adults, has yet to be incorporated early into the standard care of POMS. Objective: To screen for cognitive impairment early in the course of POMS and analyze predictive factors. Methods: Of the 955 POMS or clinically isolated syndrome (CIS) patients prospectively assessed from March 2014 to July 2018, 500 POMS and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 34 publications
(50 reference statements)
3
28
0
Order By: Relevance
“…Several studies have found that the SDMT is sensitive to progression, with greater impairments noted over time. 15 , 28 , 60 , 135 , 136 , 143 While declines in attention, processing speed, or memory were detected in several cohorts, 31 , 47 , 60 , 112 , 116 , 134 , 158 this was not observed by Wybrecht et al 50 Instead, they found a greater number of persons with MS impaired in executive functioning 10 years later, particularly on the TMT-B, Digit Spans Backwards, and both phonemic and semantic fluency. 50 Declines in executive functioning, including verbal fluency, have been noted in other longitudinal early MS cohorts.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Several studies have found that the SDMT is sensitive to progression, with greater impairments noted over time. 15 , 28 , 60 , 135 , 136 , 143 While declines in attention, processing speed, or memory were detected in several cohorts, 31 , 47 , 60 , 112 , 116 , 134 , 158 this was not observed by Wybrecht et al 50 Instead, they found a greater number of persons with MS impaired in executive functioning 10 years later, particularly on the TMT-B, Digit Spans Backwards, and both phonemic and semantic fluency. 50 Declines in executive functioning, including verbal fluency, have been noted in other longitudinal early MS cohorts.…”
Section: Resultsmentioning
confidence: 89%
“…Over time, these impairments can become more significant, with a greater number of individuals exhibiting cognitive involvement. While the SDMT has been shown to be sensitive to both initial cognitive impairment 13 , 22 , 26–28 , 30 , 31 , 33 , 34 , 36 , 41 , 44–46 , 48 , 57 , 59 , 62 , 64 , 65 , 68 , 70 , 76 , 82 , 86 , 94 , 97 , 107 , 109 , 113 , 114 , 118 , 127 , 135 , 140 , 142–144 , 148 , 151 , 156 and progression, 15 , 28 , 60 , 135 , 136 , 143 a number of longitudinal early MS cohorts demonstrated declines in executive functioning and verbal fluency, 47 , 50 , 134 signaling the importance of evaluating and monitoring these domains over time. The evidence of modifying factors is mixed; however, several studies noted a positive influence on cognitive functioning with DMT usage 91 , 93 , 100 , 120 , 151 , 154 , 155 and cognitive reserve may help protect against decline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although physical disability is rarely seen in the first decade of disease course in pediatric-onset MS (POMS) [ 1 ], cognitive impairment is fairly common in this patient population. Findings across studies showed that around one-third of pediatric MS patients suffer from some degree of cognitive impairment, and it could be detected as early as nearing disease onset in a subset of patients [ 2 , 3 , 4 , 5 ]. Multiple cognitive domains have been reported to be affected in pediatric MS, including information processing speed, attention, working memory (WM), verbal and visuospatial memory, executive function, visuo-motor integration, and aspects of language function [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Relapses in pediatric MS lead to missed school days, motor and gait impairments requiring physical or occupational therapy, and have been associated with slowed cognitive processing. 1 The adverse psychological impact of MS relapses has been well-documented in adults 2 and which may be amplified when experienced in children and adolescents, as well as impacting their families. Those with pediatric MS randomized to MS therapies less effective in controlling relapses experience (e.g.…”
mentioning
confidence: 99%